Identification of type III secretion substrates of Chlamydia trachomatis using Yersinia enterocolitica as a heterologous system - da Cunha, M. (2014)
Background: Chlamydia trachomatis is an obligate intracellular human pathogen causing ocular and urogenital infections that are a significant clinical and public health concern. This bacterium uses a type III secretion (T3S) system to manipulate host cells, through the delivery of effector proteins into their cytosol, membranes, and nucleus. In this work, we aimed to find previously unidentified C. trachomatis T3S substrates. Results: We first analyzed the genome of C. trachomatis L2/434 strain for genes encoding mostly uncharacterized proteins that did not appear to possess a signal of the general secretory pathway and which had not been previously experimentally shown to be T3S substrates. We selected several genes with these characteristics and analyzed T3S of the encoding proteins using Yersinia enterocolitica as a heterologous system. We identified 23 C. trachomatis proteins whose first 20 amino acids were sufficient to drive T3S of the mature form of β-lactamase TEM-1 by Y. enterocolitica. We found that 10 of these 23 proteins were also type III secreted in their full-length versions by Y. enterocolitica, providing additional support that they are T3S substrates. Seven of these 10 likely T3S substrates of C. trachomatis were delivered by Y. enterocolitica into host cells, further suggesting that they could be effectors. Finally, real-time quantitative PCR analysis of expression of genes encoding the 10 likely T3S substrates of C. trachomatis showed that 9 of them were clearly expressed during infection of host cells. Conclusions: Using Y. enterocolitica as a heterologous system, we identified 10 likely T3S substrates of C. trachomatis (CT053, CT105, CT142, CT143, CT144, CT161, CT338, CT429, CT656, and CT849) and could detect translocation into host cells of CT053, CT105, CT142, CT143, CT161, CT338, and CT429. Therefore, we revealed several C. trachomatis proteins that could be effectors subverting host cell processes.